2019
DOI: 10.1111/lam.13170
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of beta‐lactamase and biofilm producingEnterobacteriaceaeisolated from organized and backyard farm ducks

Abstract: This study was undertaken to detect the occurrence of beta‐lactamase and biofilm producing Enterobacteriaceae in healthy ducks. A total 202 cloacal swabs were collected from ducks kept in organized (n = 92) and backyard (n = 110) farms in West Bengal (India). The ducks had no history of antibiotic intake. Among the 87 phenotypically beta‐lactamase producing Escherichia coli, 19 (17·43%), 6 (5·05%) and 15 (13·76%) isolates possessed blaTEM, blaSHV and blaCTX‐M respectively. Whereas, 5 (38·46%) Salmonella isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 22 publications
1
23
2
Order By: Relevance
“…Occurrence of ESBL-producing Klebsiella in household animals in absence of the direct exposure to the third-generation cephalosporins can be correlated with the exposure to the environmental resistance gene pool. Earlier studies in the same geographical location revealed that the water and soil may act as source of antimicrobial resistant bacteria to the backyard pigs and ducks (Samanta et al 2015;Banerjee et al 2019). The more detailed genetic analysis exhibited that bla CTX-M gene of E. coli isolated from dogs and cats possessed a unique flanking region originated from environmental gene pool due to exposure to the contaminated environment (Maeyama et al 2018).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Occurrence of ESBL-producing Klebsiella in household animals in absence of the direct exposure to the third-generation cephalosporins can be correlated with the exposure to the environmental resistance gene pool. Earlier studies in the same geographical location revealed that the water and soil may act as source of antimicrobial resistant bacteria to the backyard pigs and ducks (Samanta et al 2015;Banerjee et al 2019). The more detailed genetic analysis exhibited that bla CTX-M gene of E. coli isolated from dogs and cats possessed a unique flanking region originated from environmental gene pool due to exposure to the contaminated environment (Maeyama et al 2018).…”
Section: Resultsmentioning
confidence: 99%
“…In India, earlier studies revealed occurrence of AmpC in Klebsiella/E. coli strains isolated from poultry, cattle with mastitis, pig and farm environment, and ducks (Samanta et al 2018;Banerjee et al 2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The backyard ducks, reared by marginal farmers in India, cannot afford to use antibiotics in feed or during therapy owing to high cost. This study provided a valuable proof that exposure to contaminated environment might be an additional source for generation of antimicrobial resistant bacteria in backyard ducks [15]. To investigate the prevalence of ESBL/beta-lactamase producing E. coli in healthy pigs, 200 rectal swabs were collected from four organized and 10 backyard farms of W.B.…”
Section: Prevalence Of Antibiotic Resistant Bacteria In Studied Animamentioning
confidence: 99%
“…19 In the past few years, several reports on the high prevalence of drug-resistant Salmonella, Campylobacter spp., and Staphylococcus aureus in animals, farms, poultry markets, dairy/dairy products, street foods, etc., in India and the Indian subcontinent have been published. 3,[20][21][22][23][24][25][26][27][28][29][30] In addition to hygiene measures and vaccination, the use of phages as an antibiotic substitute to decrease the amount of Salmonella and Campylobacter entering the food chain is gaining traction across the world. A company in India (Proteon Pharmaceuticals) has made a commercially available lineup of three phage cocktails.…”
Section: Poultry Bacterial Pathogensmentioning
confidence: 99%